Pilgrim Reverence as a Pathway to Ecological Conversion: An Analysis of Phenomenological Journaling along the Way - Muthupandiyan, Megan M. (Religions, 2023)
By fostering reverence, walking The Way can facilitate a critical tool in the promotion of what Pope Francis calls ecological conversion in his 2015 encyclical Laudato Si’. Re-reading a series of personal phenomenological reflections she wrote during the course of her 2012 and 2017 pilgrimages along the Camino Frances through the lens of philosopher Paul Woodruff’s theory of reverence, the author explores the emotional sources of reverence pilgrims experience through the course of pilgrimage. Cultivated through a body of non-religious but characteristically pilgrim-oriented ceremonies, ritual activities, and acts of perception, the pilgrim reverence the author experiences and observes does not seem to draw from any single theological lexicon; it seems rather to extend, in all cases, into and beyond a feeling for the human community, to the earth itself. It is a spiritual exercise open to humanity itself, where pilgrims have the opportunity to foster recognition that everything is connected in our social, environmental, and economic ecologies.